Surface Monocrystallization of Copper Foil for Fast Growth of Large Single‐Crystal Graphene under Free Molecular Flow. Issue 40 (26th August 2016) - Wang, Huan; Xu, Xiaozhi; Li, Jiayu; Lin, Li; Sun, Luzhao; Sun, Xiao; Zhao, Shuli; Tan, Congwei; Chen, Cheng; Dang, Wenhui; Ren, Huaying; Zhang, Jincan; et al.
Abstract : Wafer‐sized single‐crystalline Cu (100) surface can be readily achieved on stacked polycrystalline Cu foils via simple oxygen chemisorption‐induced reconstruction, enabling fast growth of large‐scale millimeter‐sized single‐crystalline graphene arrays under molecular flow. The maximum growth rate can reach 300 μm min −1, several orders of magnitude higher than previously reported values for millimeter‐sized single‐crystalline graphene growth on Cu foils.